Estratégias de estudo sob uma perspectiva da aprendizagem autorregulada: uma investigação da prática instrumental dos alunos das classes de cordas friccionadas da UFPB - Sales, Mayra Carmeli Maia (2019)
The optimization of the time devoted by students to the individual practice as an instrumentalist depends on how they conduct this process. This is a fundamental skill for making better use of available time when pursuing musical improvement. In this sense, the development of self-regulation capacity in the musical learning process, promotes the student's independence in relation to the necessary control and decision all over the study of the instrument. The main objective of this research is to investigate the routine of practice by the string instrument students at the UFPB undergraduate program in music. It is intended to verify the use of study strategies, from a self-regulated learning perspective, which could improve the effectiveness of the practice and the developing of the student´s own autonomy in this process. As a result of a bibliographic and documentary research, we present a set of strategies and study habits advocated by music authors and organized within a cyclic model of three steps of self-regulation in learning: preparation, execution and self-reflection. The information obtained at this stage was used as a start point for a questionnaire that conducted to a survey study with 38 students from the string department from the undergraduate program in music at UFPB. The results indicated that a significant number of students apply strategies related to self-regulatory processes, which favors the development of their autonomy and the effectiveness of this process as well. The preparation and execution steps have presented more positive points than the self-reflection one. It has been noticed that the progress on the self-reflection step is hindered by the lack of better attention to some details presented in the previous steps. We have also observed that some sources used as reference in this research are not known by many students. In this sense, this research can offer tools so that will allow the students not only to reflect on the way they practice, but also to apply habits and strategies which are effective for learning. This study may be also useful for teachers in the string department of the undergraduate program at UFPB and allow to them an overview of the recurring study habits used by this group of students and how they behave in relation to their individual practice.